The Secret to Successful User Communities: An Analysis of Computer Associates' User Groups - Celine Schulz (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2006)
This paper provides the first large scale study that examines the impact of both individual- and group-specific factors on the benefits users obtain from their user communities. By empirically analysing 924 survey responses from individuals in 161 Computer Associates' user groups, this paper aims to identify the determinants of successful user communities. To measure success, the amount of time individual members save through having access to their user networks is used. As firms can significantly profit from successful user communities, this study proposes four key implications of the empirical results for the management of user communities.
urn:nbn:de:bvb:19-epub-1257-2
Keywords: O32; M10; 650; Managing User Communities; Collective Action; Information Sharing